The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/21691401.2019.1709857
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary biological evaluation of 123I-labelled anti-CD30-LDM in CD30-positive lymphomas murine models

Abstract: Overexpression of CD30 has been reported on the surface of some T-cell lymphomas, especially on Hodgkin's lymphoma (HL) and anaplastic large cell lymphoma (ALCL). CD30 targeted immunotherapy has good clinical therapy response. We have produced a novel antibody drug conjugates (ADCs)-anti-CD30-LDM, which shows attractive tumour-targeting capability and extremely potent antitumor efficacy. To further investigate biological characteristics and promote clinical translation of anti-CD30-LDM, we constructed a radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Although the use of radiolabeling is undoubtedly an efficient way to address the plasma and tissue ADC profiles with a high detection threshold, it suffers from two main limitations. In almost all the studies reported so far, the radioisotopes are incorporated either into the drug or the protein, and therefore, the simultaneous in vivo monitoring of both entities is not straightforwardly achieved. Furthermore, the radiolabeling of monoclonal antibody systematically implies a random conjugation of the radioactive species within the protein core, which could lead to potential alterations of the ADC binding and biodistribution properties. …”
Section: Introductionmentioning
confidence: 99%
“…Although the use of radiolabeling is undoubtedly an efficient way to address the plasma and tissue ADC profiles with a high detection threshold, it suffers from two main limitations. In almost all the studies reported so far, the radioisotopes are incorporated either into the drug or the protein, and therefore, the simultaneous in vivo monitoring of both entities is not straightforwardly achieved. Furthermore, the radiolabeling of monoclonal antibody systematically implies a random conjugation of the radioactive species within the protein core, which could lead to potential alterations of the ADC binding and biodistribution properties. …”
Section: Introductionmentioning
confidence: 99%
“…To study its biodistribution, this conjugate was radioiodinated. After injection in CD30 + lymphoma-bearing mice, the retention of the tracer in tumor tissues was twice as high in CD30 + compared to CD30-negative tumors ( 142 ).…”
Section: Trnt For Hematological Malignanciesmentioning
confidence: 99%
“…Anti-CD30-LDM alone or combination with crizotinib has shown significant anti-tumor activity in a CD30+/ALK+ anaplastic large-cell lymphoma model [ 174 ]. Anti-CD30-LDM was radiolabeled with 123 I and demonstrated strong binding capabilities in CD30-positive cells, and a biodistribution study showed a 2-fold higher tumor uptake in CD30+ versus CD30- tumors (4.98 ± 0.99%ID/g vs. 2.75 ± 0.47%ID/g, respectively) [ 175 ]. These findings support the potential use of 123 I-anti-CD30-LDM as a companion diagnostic in the further clinical development of anti-CD30-LDM.…”
Section: Role Of Molecular Imaging In the Clinical Development Of mentioning
confidence: 99%